2013
DOI: 10.1021/ol303419b
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Electron Configuration of Iron Ion through Core Contraction of Porphyrin: Implications for Heme Distortion

Abstract: It was demonstrated experimentally that nonplanar iron porphyrins can be induced to undergo a conversion in their electronic configuration to form a cross-hybrid transition by compressing the macrocyclic core size for the central metal ion. A series of monostrapped iron porphyrins were used as model systems, and their electronic properties were probed using electron spin resonance and differential spectral analyses. These results indicate that the formation of a cross-hybrid transition stage is related to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 30 publications
4
46
1
Order By: Relevance
“…A clear spectral deviation occurs between 1 ‐Cu and 2 ‐Cu. This deviation indicates conversion of the electron configuration of the Cu II ion, as shown in our previous reports for iron, and cobalt, and also indicates that a core size of ca. 3.85 Å is a critical value in the conversion of the electronic structure of the Cu II ion.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…A clear spectral deviation occurs between 1 ‐Cu and 2 ‐Cu. This deviation indicates conversion of the electron configuration of the Cu II ion, as shown in our previous reports for iron, and cobalt, and also indicates that a core size of ca. 3.85 Å is a critical value in the conversion of the electronic structure of the Cu II ion.…”
Section: Resultssupporting
confidence: 80%
“…Distorted heme can hydroxylate inactivated C–H bonds, and the nonplanarity of heme is important in heme chemistry . Our recent studies have shown that the 3d electronic structure of the metal center can be tuned by macrocyclic deformations and the resulting change in the core size, and this tuning is related to the specific properties of the distorted heme . It has been proven indirectly that the activation of oxygen in heme and the reaction of the activated oxygen are two independent processes .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the N 4 cavity contraction was suggested to increase the electron cloud density of a complexed metal ion, which was suggested to drive the formation of higher valent iron species. 62 While it is unclear how these factors influence catalysis, the present and previous studies indicate that significant deformations are present during carbene transfer. For example, DFT optimization of a species that is active for carbene transfer, Ir(TTP)CH 3 (C(Ph)CO 2 CH 3 ), revealed notable porphyrin distortion in the ruffling (−0.4513) and doming (−0.2309) modes, with an overall D oop of 0.5154.…”
Section: Synthesis and Characterization Of Diaminocarbenementioning
confidence: 60%
“…Indeed, the porphyrin core of metalloporphyrins is known to display more distortion and deformation modes than their free-base analogues (the latter most usually having a flatter structure than the former) in order to accommodate the metal ion into the cavity, which impacts on the Gibbs activation energies (DG°) of conformational processes, such as rotations. [67][68][69][70][71] Similarly to S0, the b-pyrrolic proton signal of S1 splits from one (room temperature) into two distinct singlets at 203 K (D 2d !D 2 symmetry), which has also been attributed to the slowing down of the NH tautomerism process (Figure 8, right). Also in this case, the signal of the b' protons is broader than that of the b'' protons (full width at half maximum, FWHM = 5.4 and 3.8 Hz, respectively), which is indicative of long-range couplings 4 J(N-H/b'-H) in the former.…”
Section: Variable-temperature Nmr Experimentsmentioning
confidence: 99%